Education and screening for obesity, hypertension, and diabetes (including gestational diabetes) "at the doorstep" of women from nine underprivileged urban areas in Delhi National Capital Region. Issue 5 (September 2021) - Gopalan, Hema S.; Haque, Intazaamul; Ahmad, Shamshad; Gaur, Ashok; Misra, Anoop
Abstract: Background and aims: Women in underprivileged urban areas have poor access to health and education, making them vulnerable to non-communicable diseases (NCDs), specifically diabetes. The current project has sought to focus on this group, to educate and screen this population to prevent and manage obesity and diabetes. Methods: The project was conducted in 9 underprivileged areas of Delhi NCR using a mobile van unit. Women from these areas were invited for health education (this included talks, lectures and distribution of Information, Education & Communication material), screening anthropometric, blood glucose and blood pressure (BP) measurements diet counselling sessions and referral of subjects with uncontrolled blood glucose. Results: Baseline survey on knowledge of diabetes and nutrition showed low awareness. Health education sessions (n, 46) included face-to-face discussion and problem solving and distribution of simple pictorial leaflets (n, 3000). The health education sessions were well accepted. In total, 4% women (n, 3175/91000- total population, 3056 non-pregnant, 119 pregnant) participated in the research trial. Among non-pregnant women, an average weight gain of 11.8 kg between the ages of 20–40 years was observed. The average BMI and waist circumference (WC) was 26.8 ± 5.3 kg/m 2 and 91.1 ± 13.2 cm, respectively in non-pregnant women. Further, 75.3.0% (2207/2928) and 96.7% (2875/2971) of the non-pregnant women had overweight/obesity and abdominal obesity, respectively. In the non-pregnant women, 21.7% had known diabetes. Further, 7.4% non-pregnant women and 2.5% pregnant women were identified as having hyperglycaemic state. Hypertension was observed in 11.9% pregnant women and 49.9% of non-pregnant women. Conclusion: Extremely high prevalence of obesity, along with diabetes and hypertension in underprivileged urban women requires intensive individualised and group health education, screening, and counselling "at the doorsteps", as has been shown in our model. Highlights: Health education sessions were undertaken in 9 underprivileged areas of Delhi. Overweight/obesity and abdominal obesity was seen in 74.0% and 96.7% of the non-pregnant women, respectively. Among non-pregnant women, 21.7% had diabetes. Additionally, 7.4% of these women and 2.5% pregnant women had hyperglycaemia. Hypertension was observed in 11.9% pregnant women and 49.9% of non-pregnant women.